2008
DOI: 10.1086/589663
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the Incentive Properties of Share Contracts

Abstract: Ever since Adam Smith, share contracts have been condemned for their lack of incentives. Sharecropping tenants face incentives to undersupply productive inputs since they receive only a fraction of the marginal revenue. The empirical literature reports that lands under sharecropping are indeed less productive and employ inputs less intensively than those operated by owners. This paper shows that (1) sharecropping and fixed-rent tenancy are both associated with low-quality lands, (2) plots under sharecropping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Some empirical studies have found sharecropping to be efficient when the social distance between respective parties is low. This includes contracts that are made among kin (Sadoulet et al, 1997), contracts of patron–client relations 3 (Bardhan and Rudra, 1980; Hayami and Kikuchi, 1990), or when observed and unobserved plot characteristics are taken properly into account (Braido, 2004). Empirical studies that found sharecropping to be inefficient are usually when policy limits contract choice in some way (Otsuka, 2002).…”
Section: The Discourse On Sharecropping Efficiencymentioning
confidence: 99%
“…Some empirical studies have found sharecropping to be efficient when the social distance between respective parties is low. This includes contracts that are made among kin (Sadoulet et al, 1997), contracts of patron–client relations 3 (Bardhan and Rudra, 1980; Hayami and Kikuchi, 1990), or when observed and unobserved plot characteristics are taken properly into account (Braido, 2004). Empirical studies that found sharecropping to be inefficient are usually when policy limits contract choice in some way (Otsuka, 2002).…”
Section: The Discourse On Sharecropping Efficiencymentioning
confidence: 99%
“…Marshall (1920) considers share tenancy as an inefficient practice of cultivation where resources are suboptimally utilized. The argument behind the inefficiency of sharecroppers is that the farmers are not interested in utilizing their effort optimally because a large portion of output goes to the landlord (Tesafa and Abera, 2014;Braido, 2008). In contrast to the Marshallian inefficiency argument, Johnson (1950) advocates that the tenant may induce to apply the efficient level of input if there is continuous monitoring of the landowners regarding the cultivation practice.…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee et al (2002) found that relatively more land rights that lead to improved crop shares and higher security of tenure for tenants may have a positive effect on productivity. Several studies (Braido, 2008;Dubois, 2002) found that the land leased out to the tenant might be of less fertile than that is cultivated by owner farmers, and thus, sharecropping is relatively inefficient. Goswami (2015) found that the sharecroppers do not consider the productivity enhancing strategy and they are reluctant to use the sufficient amount of input in agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Braido (2008) empirically finds a strong inverse relation between tenancy and land quality, but he does not provide theoretical explanations for it.…”
mentioning
confidence: 92%